"Evaluation of safety margin" in ameloblastoma of the mandible by surgical, radiological, and histopathological methods: An evidence-based study - S Kalaiselvan; A V Dharmesh Kumar Raja; B Saravanan; A Srivel Vigneswari; Ramesh Srinivasan (Wolters Kluwer Medknow Publications, 2016)
Objective: The purpose of this study is to elicit the amount of safety margin necessary around the ameloblastic lesion in view of preventing further recurrence. Materials and Methods: The study consisted of 25 cases of mandibular ameloblastoma. Diagnosis was based on clinical and radiological analysis and confirmed by histopathological report. An incisional biopsy was done preoperatively to confirm the diagnosis. Segmental resection was planned for all the cases. After the resection, postoperative panoramic radiograph of the specimen was taken followed by histopathological examination of its margin to detect tumor cell infiltration. Results and Conclusion: In all our cases, the ameloblastoma was infiltrating in nature. A follow-up period of 10 years showed neither recurrence nor implant failure. In our study, we conclude our safe margin for infiltrating variant of ameloblastoma based on histopathological report of the resected specimen.